Kewenangan DPRD Dan Kepala Daerah Dalam Menetapkan Peraturan Daerah - Rosianti, Elshi Elvira; Hafizd, Jefik Zulfikar; Rana, Mohamad; Sugianto, Sugianto (STAI Bumi Silampari, 2024)
The Regional People's Representative Council (DPRD) of Kuningan Regency plays a crucial role in the formation of Regional Regulations, as stipulated in Article 41 of Law Number 32 of 2004, which mentions the functions of legislation, budgeting, and supervision for DPRD. However, in practice, DPRD tends to propose fewer Regional Regulations than the regional heads each year. Based on this, this research aims to assess the implementation of the authority held by the DPRD of Kuningan Regency based on Law No. 12 of 2011 and Regional Regulation (Perda) of Kuningan Regency No. 21 of 2013 concerning the Guidelines for the Formation of Local Legal Products. Additionally, the objective of this research is to understand the fiqih siyasah perspective on the authority of the DPRD and the Regional Head of Kuningan Regency in forming Regional Regulations. This field research employs an empirical juridical approach using data collection methods such as observation, interviews, and documentation. Data analysis involves processing, presenting, and verifying the gathered information. The findings indicate that the determination of Kuningan Regency's Regional Regulations is achieved through the agreement between the DPRD and the Regional Head. Thus, both the DPRD and the Regional Head have equal positions in establishing Regional Regulations. However, the implementation of the DPRD's authority to form Regional Regulations has not been optimal. During the period 2020-2021, Regional Regulations were predominantly proposed by the Regional Government. From a fiqih siyasah perspective, such authority should be held by a representative institution capable of channeling the aspirations of the community.